Features fruit set higbush blueberry depending on the cultivar specifications and weather and climatic conditions - Drozd, Olga V. (Experimental Biology and Biotechnology, 2022)
On the basis of four-year data, the features of fruit set are shown for 15 cultivars of highbush blueberry. The average yield of ripe berries from the number of flowers varies within a fairly wide range and averages from 46 % (Chandler) to 83 % (Sunrise) for highbush blueberry cultivars. The degree of variability in berry setting indices in the taxa under study varied significantly over the years: from a low level (Bluejay, Nui, Puru, Spartan, Sunrise) to a very high level (Bonus). It was revealed that the lower the level of variability of the fruit setting indicator, the higher the adaptive ability of the taxon to changing weather and climatic conditions. The setting of highbush blueberry fruits is influenced by such weather and climatic factors as humidity and air temperature. Precipitations falling within the range close to the mean annual values or slightly higher than them, and the air temperature close to the climatic norm, contribute to better fruit setting. A pronounced shortage of precipitation, especially against the background of an increased average daily temperature, during flowering and growth of fruits, as well as heavy precipitation during the period of mass flowering of blueberries, have a negative effect on berry setting. At the same time, the main limiting temperature factor during flowering and formation of blueberry fruits is a decrease in air temperature to minus indicators (freesing).
Keywords: highbush blueberry; Vaccinium corymbosum; introduction; pollination on flowers; fruit set; meteorological conditions; Belarus